Psychosocial problems and barriers to improved diabetes management: results of the Cross-National Diabetes Attitudes, Wishes and Needs (DAWN) Study. - Peyrot, M; Rubin, R; Lauritzen, T; Snoek, F; Matthews, DR; Skovlund, SE (2005)
AIMS: To examine patient- and provider-reported psychosocial problems and barriers to effective self-care and resources for dealing with those barriers. METHODS: Cross-sectional study using face-to-face or telephone interviews with diabetic patients and health-care providers in 13 countries in Asia, Australia, Europe and North America. Participants were randomly selected adults (n = 5104) with Type 1 or Type 2 diabetes, and providers (n = 3827), including primary care physicians, diabetes specialist physicians and nurses. RESULTS: Regimen adherence was poor, especially for diet and exercise; provider estimates of patient self-care were lower than patient reports for all behaviours. Diabetes-related worries were common among patients, and providers generally recognized these worries. Many patients (41%) had poor psychological well-being. Providers reported that most patients had psychological problems that affected diabetes self-care, yet providers often reported they did not have the resources to manage these problems, and few patients (10%) reported receiving psychological treatment. CONCLUSIONS: Psychosocial problems appear to be common among diabetic patients worldwide. Addressing these problems may improve diabetes outcomes, but providers often lack critical resources for doing so, particularly skill, time and adequate referral sources.